Stimulasi Kognitif Berbasis Permainan Puzzle Anak Usia Pra Sekolah dengan Stunting terhadap Tugas Perkembangan - Andi Hayyun Abiddin; Agus Khoirul Anam (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Stunting causes physical development to be hampered but also threatens cognitive development which has an impact on decreasing children's productivity in adulthood. One effort that can be made is to provide cognitive stimulation to children. To determine the cognitive stimulation based on puzzle games on the learning achievement of preschool children with stunting according to the developmental stage in areas prone to volcanic disasters. This quantitative study uses a one group pretest-posttest design. The population in this study were all preschool children in disaster-prone areas in Kepanjenkidul sub-district, 42 people who were diagnosed with stunting by the Kepanjenkidul Health Center UPT, Blitar City. The number of samples was 30 people, and the sampling technique used was proportional stratified random sampling with the following sample criteria: (1) children who are categorized as stunting based on BMI results according to height/age and weight/age measurements, (2) willing to be respondents, (3) physically and mentally healthy. This study used observation sheets for preschool children's developmental tasks covering social emotions, physical motor skills, cognitive skills, and language skills with criteria of very well developed (BSB) with a score of 4, developing according to expectations (BSH) with a score of 3, starting to develop (MB) with a score of 2, and not yet developed (BB) with a score of 1. Observations were conducted twice (pre and post test); (1) giving puzzles to respondents and observing them according to developmental tasks; (2) providing education related to puzzle games that include developmental tasks; (3) asking respondents to play the puzzle again and observe it. After the data was collected, the data was analyzed using the Wilcoxon test (p0.05). The results of the study showed that there were changes in developmental tasks between before and after being given cognitive stimulation based on puzzle games which included social emotional development tasks (p-value = 0.001), physical motor (p-value = 0.002), cognitive (p-value = 0.001) and language (p-value = 0.000). .Stunting can interfere with children's cognitive development, which causes a decrease in cognitive abilities. Puzzle games can affect the development of fine and gross motor skills in preschool children. Health services should increase interventions to stimulate the cognitive abilities of preschool children with stunting and conduct regular observations. Keywords: Stunting, Education, Puzzle, Disaster.   ABSTRAK Stunting menyebabkan terhambatnya perkembangan fisik tetapi juga mengancam perkembangan kognitif yangberdampak pada penurunan produktivitas anak di masa dewasa. Salah satu upaya yang dapat dilakukan adalah memberikan stimulasi kognitif pada anak. Mengetahui stimulasi kognitif berbasis permainan puzzle pada prestasibelajar anak usia pra sekolah dengan stunting sesuai dengan tahap perkembangan di kawasan rawan bencana gunungberapi.Penelitian kuantitatif ini menggunakan one group pretest-posttest design. Populasi dalam penelitian ini adalahseluruh anak usia pra sekolah di kawasan rawan bencana di kecamatan Kepanjenkidul 42 orang yang terdiagnosa stunting oleh UPT Puskesmas Kepanjenkidul Kota Blitar. Jumlah sampel sebanyak 30 orang, dan teknik pengambilansampel yang digunakan adalah proportional stratified random sampling dengan kriteria sampel sebagai berikut: (1)anak  yang masuk kategori stunting berdasarkan hasil BMI menurut pengukuran tinggi badan/umur dan beratbadan/umur, (2) bersedia menjadi responden, (3) sehat jasmani dan rohani. Penelitian ini menggunakan lembar observasi tugas perkembangan anak usia pra sekolah yang meliputi sosial emosi, fisik motorik, kognitif, dan bahasa dengan kriteria berkembang sangat baik (BSB) skor 4, berkembang sesuai harapan (BSH) skor 3, mulai berkembang (MB) skor 2 dan belum berkembang (BB) skor 1. Observasi dilakukan sebanyak dua kali (pre dan post test); (1) memberikan puzzle pada responden dan diobservasi sesuai dengan tugas perkembangan;  (2) memberikan edukasi terkait permainan puzzle yang mencakup tugas perkembangan; (3) meminta responden untuk memainkan kembali puzle tersebut dan mengobservasinya. Setelah data terkumpul, data dianalisis menggunakanWilcoxon test (p0.05). Hasil penelitian menunjukkan bahwa terdapat perubahan tugas perkembangan antara sebelum dan diberikan stimulasi kognitif berbasis permainan puzzle yang meliputi tugas perkembangan sosial emosi (p-value = 0,001), fisik motorik (p-value = 0,002), kognitif (p-value = 0,001) dan bahasa (p-value = 0,000). Stunting dapat mengganggu perkembangan kognitif anak, yang menyebabkan penurunan kemampuan kognitif. Permainan puzzle dapat mempengaruhi perkembangan keterampilan motorik halus dan kasar anak prasekolah. Pelayanan kesehatan sebaiknya meningkatkan intervensi untuk menstimulasi kemampuan kognitif anak prasekolah dengan stunting dan melakukan observasi secara berkala. Kata Kunci: Stunting, Edukasi, Puzzle, Bencana.